Age as a moderator of motivational interviewing and nondirective client‐centered psychotherapy for alcohol use disorder: An exploratory study. (5th March 2023) - Kuerbis, Alexis; Behrendt, Silke; Morgenstern, Jon
Abstract: Background: Motivational interviewing (MI) is a widely used intervention applied to a host of health behaviors, including alcohol consumption among individuals with alcohol use disorder (AUD). Age is an underexplored moderator of MI for treating AUD, with the impact of comparing older individuals with their younger counterparts virtually unexplored. Also unexplored is whether age is associated with distinct mechanisms of change (e.g., motivation and self‐efficacy) within treatment. Methods: This secondary data analysis utilizes combined data from two previous studies (total N = 228) that both aimed to test MI's mechanisms of action in the context of a goal for moderated drinking. Both studies had three conditions: MI, nondirective listening (NDL), and a self‐change condition (SC). In the current analyses, the moderating impact of continuous age and age group, <51 (younger adults, YA) versus ≥51 (older adults, OA), on the impact of MI on alcohol use compared to NDL and SC were tested using generalized linear models. Age differences in confidence and commitment to reduce heavy drinking during treatment were also explored. Results: Age group by condition differences emerged, where NDL significantly reduced drinking among YA but not OA (mean −12 vs. −3 standard drinks, respectively). Among OA, MI outperformed NDL but not SC, though the effect was weak. Confidence and commitment during treatment were not significantly different across age‐by‐condition groups. Conclusion: Findings underscore the importance of understanding the impact of age on treatment effectiveness, as providing a nondirective intervention for OA with AUD could provide suboptimal treatment. Further research is needed to explore these differential effects. Abstract : The impact of age on Motivational Interviewing (MI) on heavy alcohol use is underexplored. Adults 51+ who drink heavily assigned to MI significantly reduced their drinking but only slightly more than those in a non‐directive listening (NDL) condition. Age differences emerged in NDL; adults 50 and younger reduced their drinking by almost three times that of the older adults. Age and/or life stage may impact MI and the efficacy of other brief treatments.